Dorsal Pigmentation and Its Association with Functional Variation in MC1R in a Lizard from Different Elevations on the Qinghai–Tibetan Plateau. (23rd October 2020) - Jin, Yuanting; Tong, Haojie; Shao, Gang; Li, Jiasheng; Lv, Yudie; Wo, Yubin; Brown, Richard P; Fu, Caiyun
Abstract: Identification of the role of the MC1R gene has provided major insights into variation in skin pigmentation in several organisms, including humans, but the evolutionary genetics of this variation is less well established. Variation in this gene and its relationship with degree of melanism was analyzed in one of the world's highest-elevation lizards, Phrynocephalus theobaldi from the Qinghai–Tibetan Plateau. Individuals from the low-elevation group were shown to have darker dorsal pigmentation than individuals from a high-elevation group. The existence of climatic variation across these elevations was quantified, with lower elevations exhibiting higher air pressure, temperatures, and humidity, but less wind and insolation. Analysis of the MC1R gene in 214 individuals revealed amino acid differences at five sites between intraspecific sister lineages from different elevations, with two sites showing distinct fixed residues at low elevations. Three of the four single-nucleotide polymorphisms that underpinned these amino acid differences were highly significant outliers, relative to the generalized MC1R population structuring, suggestive of selection. Transfection of cells with an MC1R allele from a lighter high-elevation population caused a 43% reduction in agonist-induced cyclic AMP accumulation, and hence lowered melanin synthesis, relative to transfection with an allele from a darker low-elevation population. The high-elevation allele led to less efficient integration of the MC1R protein into melanocyte membranes. Our study identifies variation in the degree of melanism that can be explained by four or fewer MC1R substitutions. We establish a functional link between these substitutions and melanin synthesis and demonstrate elevation-associated shifts in their frequencies.